ANALYSIS OF THE LEVEL OF INCLUSIVE DEVELOPMENT IN UKRAINIAN IT INDUSTRY - Victor Kloba (Three Seas Economic Journal, 2025)
The research article analyzes the inclusive development of the IT industry in Ukraine. Inclusivity implies the availability of economic growth results for all citizens and taking into account the individual needs of citizens in the process of forming directions of economic development. In world practice, the Inclusive Development Index is calculated based on indicators characterizing economic growth. The IT industry in Ukraine is a promising sector of the economy, characterized by profitability, export orientation and rapid growth rates. The inclusive development of the IT industry depends on a significant number of factors, for example: the instability of the economic, political and security situation in Ukraine, as a result of a full-scale war, the world recession, the variability of legislation and tax policy. The development of the IT industry in Ukraine was studied through an assessment of the market for information equipment, services and technologies, and software. The largest number of business entities in the IT market is engaged in computer programming, consulting and related activities, and the number of such companies is growing every year. This gives grounds to argue that programming is a promising type of activity in Ukraine. A significant share in the structure of the IT sector belongs to companies engaged in the provision of information services, including data processing, posting information on websites and related activities, development and support of web portals and other information services. The IT industry in Ukraine is showing a growth trend, which is primarily confirmed by the growth in number of service providers and manufacturers of goods in this segment. Over the 10-year analyzed period, the number of providers of computer programming, consulting and related activities increased by 2.94 times, the number of computer game manufacturers increased by 1.78 times, the number of business entities providing information services increased by 2.98 times. The inclusiveness of information technologies for Ukrainian society was studied through an analysis of the: accessibility of the Internet for citizens, inclusiveness of state web services number of users of mobile operator services. The inclusiveness of state online resources continues to grow; by the end of 2023, 23% of official websites of state authorities reached a sufficient and high level of accessibility for people with hearing, vision, and musculoskeletal disorders. Inclusive development of the IT industry is an important component of the Digital Transformation Strategy of Ukraine, which aims to develop an inclusive, accessible and effective social sphere in Ukraine through the integration of digital technologies and innovations.